Combining ability estimates in maize (Zea mays L.) Through line × tester analysis (Bangladesh Journal of Agricultural Research, 2017)
Eighteen advanced S4 lines of maize extracted from NK46 were evaluated through line × tester method by using two testers for grain yield and its components. General combining ability (GCA) and specific combining ability (SCA) effects of crosses were determined to evaluate the prospective inbred lines. Highly significant genotypic differences for all of six characters, i.e. days to 50% tasselling, Days to 50% silking, plant height, ear height, 1000 kernel weight, and yield indicated presence of wide range of variability among the genotypes for those traits. Non-additive gene action was predominant. Four lines for days to 50% tasselling, one for days to 50% silking, two for plant height, one for ear height, three for 1000 kernel weight, and four for yield were found with significant GCA effects in desired direction. For days to tasselling, days to silking, plant height and ear height, none of 36 cross combinations confirmed significant SCA effects. Five combinations showed significant positive SCA effects for 1000 kernel weight. For yield two crosses showed significant positive SCA. Considering the results of present study, based on GCA and SCA analysis of observed characters seven lines namely, NK46-2, NK46-4, NK46-10, NK46- 13, NK46-18, NK46-43 and NK46-44 were selected for further breeding programBangladesh J. Agril. Res. 42(3): 425-436, September 2017